MASLD and aspartame: are new studies in the horizon? - Sergi, Consolato M. (Frontiers in Medicine, 2023)
Fatty liver disease has been on the rise in the past few decades, and there is no hope that it will stop. The terminology change that has been recently proposed may not be sufficient to advocate for a reduction of steatogenic foods and a change in lifestyle. A course change may be supported by the recent labeling of aspartame sweetener as a possible carcinogenic compound by the International Association for Research on Cancer (IARC), an agency of the World Health Organization (WHO). Aspartame sweeteners and other edulcorating molecular compounds besides colorings may trigger liver cancer other than fatty liver disease, despite limited data supporting it. An essential bias in human cohort studies is indeed the exclusion of all confounding factors, which may be barely impossible for human studies. In this perspective, we suggest that the activation of the NOD-like receptor-enclosing protein 3 (NLRP3) inflammasome and the stimulation of the tumor suppression gene TP53 may be critical in the progression from fatty liver to liver inflammation and liver cancer. Aspartame reduces a transcriptional coactivator, precisely the peroxisomal proliferator-initiated receptor-γ (gamma) coactivator 1-α (alpha) (or PGC1α). This coactivator upregulates mitochondrial bioformation, oxidative phosphorylation, respiratory capacity, and fatty acid β-oxidation. Aspartame acts in this way, probably through the activation of TP53. These events have been accountable for the variations in the lipid outline in serum and total lipid storage as well as for the impairment of gluconeogenesis in the liver, as supported by the downregulation of the gluconeogenic enzymes in experimental animals, and may be relevant in humans as well.